Legal Study Of Making An Electronic Notary Deed - Muhamad Nastain; Setyawati Setyawati (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
The Research Objectives Are: 1) Describe the Legal Study of Electronic Notary Deed issued by the Directorate General of the Ministry of Law and Human Rights. 2) Describe the Implementation, and Constraints of Electronic Notary Deed issued by the Directorate General of the Ministry of Law and Human Rights, while the data used in this study are Secondary data consisting of Primary Legal Materials and Secondary Legal Materials which are then analyzed by descriptive analysis methods.Based on the results of data analysis concluded that: 1) Notaries as Officials who carry out part of the State Function are required to provide maximum Public Services in Legal Services. Through the role of the Directorate General of General Law Administration, the Notary was given the convenience of carrying out his duties related to the Making of Electronic Deed through the AHU Online Application and in carrying out the making of the Electronic Notary Deed not in violation of Act No. 25 of 2009 On Public Services. 2.) Despite the ease in providing public services, there are still obstacles in the implementation of the making of electronic deeds, which include server problems that are often down and human resources who are not yet competent to run them.